1979
DOI: 10.1177/0310057x7900700208
|View full text |Cite
|
Sign up to set email alerts
|

Althesin for Neuroanaesthesia

Abstract: Altlzesin was lIsed as an induction agent then diluted and administered as a controlled infusion for 60 patients undergoing 66 procedures. Incremental doses of fentanyl were given to provide additional analgesia. There was delayed awakening in 7 patients (12.1%),3 of whom responded rapidly to narcotic reversal with naloxone. Intracerebral pathology and surgical trauma contributed to the slow recovery in the other 4 patients. Evidence is presented that A lthesin infusions reduce the narcotic requirement. A lthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In conclusion, this study has confirmed the results of Ramsay et al 2 that alphaxalone/alphadolone as an infusion is safe and effective for sedation of intensive care patients. In addition, the effect of this agent on lipoprotein electrophoretic pattern and its delayed return to normal have been demonstrated.…”
Section: Other Drugs and Evaluation Of Sedationsupporting
confidence: 90%
“…In conclusion, this study has confirmed the results of Ramsay et al 2 that alphaxalone/alphadolone as an infusion is safe and effective for sedation of intensive care patients. In addition, the effect of this agent on lipoprotein electrophoretic pattern and its delayed return to normal have been demonstrated.…”
Section: Other Drugs and Evaluation Of Sedationsupporting
confidence: 90%
“…4) Thc efficacy of Althesin as described in this case confirms the report of Chin, Havill and Rothwcll (1979), and disputes the consideration that Althesin is contraindicated in epilepsy. It is also significant that one of the authors in a recently completed clinical trial using Althesin infusion as an anaesthetic agent for intracranial operations found no increase in the incidence of EEG abnormalities or convulsions in the perioperative or postoperative periods (Saady 1979). Thus, unlike methohexitone, Althesin does not appear to facilitate an epileptic focus.…”
Section: Discussionmentioning
confidence: 99%